Behavioral tagging: A novel model for studying long-term memory. (September 2016) - Vishnoi, Shruti; Raisuddin, Sheikh; Parvez, Suhel
Highlights: Synaptic and capture hypothesis has been proposed to describe the synaptic changes that occur during memory formation. Behavioral Tagging relies on the setting of a learning tag and the synthesis of plasticity related proteins. Tagging explains that how a learning tag produced as a result of weak training can be paired up with PRPs and can lead to long lasting memories. This model provides an important platform to study and analyze memory. It offers a consistent structure able to define promotion, modulation, and interference in the formation of lasting memories. Abstract: New information acquired by our brain is stored in the form of two types of memories: short term memory (STM) and long term memory (LTM). Initially, Synaptic and Capture hypothesis has been proposed to describe the synaptic changes that occur during memory formation. However, recently Behavioral Tagging hypothesis was proposed that relies on the setting of a learning tag and the synthesis of plasticity related proteins (PRPs). Behavioral Tagging has its roots in Synaptic and Capture hypothesis. It seeks to explain that how a learning tag produced as a result of weak training can be paired up with PRPs (formed as a result of novelty) and can lead to long lasting memories. We have focused on describing behavioral paradigms that have been used for establishing the model of "Behavioral Tagging" and the molecules which qualify for potential PRP candidature.